Impact of institutional enviroment on the existence of fast-growing business in time of economic disturbances - Valenteová, Katarína; Čukanová, Miroslava; Steinhauser, Dušan; Sidor, Ján (Univerzita Pardubice, 2018)
As a result of the economic crisis is the restoration of economic growth and job creation one of the main aim of economic policy. Economic growth and employment can be achieved throw the creations of conditions for increasing business competitiveness. We assume that there is a positive relationship between economic freedom, innovation, and the share of high-growing enterprises in the total number of enterprises. In this paper, we used a pair linear regression analysis between variables in which our assumptions are verified.
Keywords: institutional environment; innovation; high-growing enterprises; small and medium-sized enterprises; L50; O44; L25